مكانة اللغة العربية في دستور جمهورية العرق لسنة 2005: دراسة مقارنة - حسين، كمال علي (جامعة بغداد - كلية القانون, 2020)
صرح دستور جمهورية العراق لسنة 2005 النافذ واقتداء بمعظم الدساتير العراقية السابقة ودساتير الدول العربية، بأن اللغة العربية هي اللغة الرسمية للدولة، إقرارا بالمكانة العظيمة والسامية لها، فهي اللغة التي قدسها الخالق (عز وجل)، باختيارها لغة لخاتم كتبه السماوية والمهيمن عليها جميعا (القرآن الكريم)، واصطفائها لسانا لخاتم أنبيائه وقائد رسله، حضرة الرسول الأعظم محمد بن عبد الله (صل الله عليه وسلم)، وهذا ما استوجب دراسة قواعد هذا الترسيم الدستوري للغة العربية في العراق، إضافة إلى التشريعات ذات الصلة بها، مع بحث الوضع الدستوري الخاص باللغات الأخرى في العراق، كالكردية والسريانية والتركمانية والأرمنية، كونها تتشارك مع اللغة العربية بعدها لغات للشركاء الأخرين مع الناطقين بالعربية، في الطيف العراقي الواسع الألوان.
The Constitution of the Republic of Iraq for the year 2005, in force and following most of the previous Iraqi constitutions and the constitutions of the Arab countries, states that Arabic is the official language of the state. Recognition of the great and lofty status of it, it is the language sanctified by the Creator (Almighty), by choosing a language not written by Heaven and the dominant of them all (the Holy Quran). In addition, it is also the endowment of lingual to the seal of his prophets and the leader of his messengers, the greatest Prophet Muhammad bin Abdullah (peace be upon him). Moreover, this is what questioned the study of the rules of this constitutional demarcation of the Arabic language in Iraq. In addition to the relevant legislation, it examines the special constitutional status of the other language in Iraq such as Kurdish, Syriac, Turkmen and Armenian. As they share the Arabic language with Arabic (the languages) of the other partners with Arabic speakers in the broad spectrum of Iraq.
Keywords: السياسة اللغوية -- اللغة العربية -- القوانين والتشريعات -- العراق